Dampak Pengeluaran Pemerintah Terhadap Pertumbuhan Ekonomi dan Indeks Pembangunan Manusia di Perbatasan Indonesia - Putra, Windhu (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2017)
The purpose of this study is to analyze the effect of government spending - for building infrastructures, education and health - on economic growth and Indonesian community welfare that reside along the borderline during the period of 2007 to 2014. The data used in this research is panel data. Applying estimation model of Ordinary Least Square (OLS), this research indicates that government expenditures for infrastructures and education created significant effect oneconomic growth while the expenditure for healthcare did not significantly affect the economic growth. However, in the case of people welfare, government spending on infrastructure and economic growth showed a significant effect on it, butthe government spending for education and healthcare had insignificant impact on human development index.